Molecular parameters including fluorination program order during hierarchical helical self-organization of self-assembling dendrons. (August 2022) - Peterca, Mihai; Imam, Mohammad R.; Dulcey, Andres E.; Morimitsu, Kentaro; Xiao, Qi; Maurya, Devendra S.; Percec, Virgil
Highlights: hierarchical perfluorinated helical column assembly mediated by molecular parameters; apex molecular parameters such as H-bonding and no-H-bonding; linear hydrogenated and fluorinated and branched hydrogenated alkyls on periphery; self-assembly of perfluorinated helical porous columns; new molecular parameters inducing Frank-Kasper phases; Abstract: Primary structure endows tertiary structure while tertiary structure determines function. This fundamental principle is responsible for the generation of high order and precise functions in both biological assemblies including giant and mega proteins and nucleic acids as well as in metals generated from only few atoms. However, this size-independent ability to generate high order and very precise functions is not yet accessible in non-biological assemblies that use the same principles for their hierarchical self-organization. Here we report a study investigating the role of the molecular parameters on the hierarchical self-organizations of helical columnar assemblies produced from the column-forming self-assembling dendron (4-3, 4-3, 5)-X with a linear or branched hydrogenated or linear semifluorinated alkyl groups while apex is -CO2 CH3 or -CH2 OH. A combination of differential scanning calorimetry, small and wide-angle powder and oriented fiber X-ray diffraction experiments together with helical diffraction theory, 2-D and 3-D electron density maps were employed in these structural analysis experiments. They demonstrated that H-bonding at the apex of the self-assembling dendron enhanced the order of the helical columns by comparison with the order of supramolecular helical columns based on dendrons containing an ester group at their apex. This was the case for both linear and branched alkyl groups at the periphery of the self-assembling dendron. Unexpectedly, self-assembling dendrons containing semifluorinated alkyl groups on their periphery and H-bonding groups at their apex increase even more the order of their supramolecular perfluorinated porous helical column. In all cases helix is mediated by the aromatic part of the dendron but hierarchically influenced both by the apex and peripheral groups. A combination of branched alkyl groups with H-bonding at the apex produced a new mechanism to transform helical columns assembled from the column-forming (4-3, 4-3, 5)-X self-assembling dendron into spherical assemblies, organized from conical dendron conformers, forming an A15 Frank-Kasper phase. Graphical Abstract: Graphical Abstract Image, graphical abstract .